2017
DOI: 10.1159/000480738
|View full text |Cite
|
Sign up to set email alerts
|

The Missing Link in the Pathophysiology of Vascular Cognitive Impairment: Design of the Heart-Brain Study

Abstract: Background: Hemodynamic balance in the heart-brain axis is increasingly recognized as a crucial factor in maintaining functional and structural integrity of the brain and thereby cognitive functioning. Patients with heart failure (HF), carotid occlusive disease (COD), and vascular cognitive impairment (VCI) present themselves with complaints attributed to specific parts of the heart-brain axis, but hemodynamic changes often go beyond the part of the axis for which they primarily seek medical advice. The Heart-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 67 publications
0
70
0
Order By: Relevance
“…Various scans for both the brain and the heart were acquired at each of the centers. For details about the scans acquired and the selection criteria for the subjects the readers are referred to the publication of van Buchem et al [22] and to the study design publication of Hooghiemstra et al [25]. The institutional review board approved this study, and all patients were informed and provided written consent.…”
Section: Methodsmentioning
confidence: 99%
“…Various scans for both the brain and the heart were acquired at each of the centers. For details about the scans acquired and the selection criteria for the subjects the readers are referred to the publication of van Buchem et al [22] and to the study design publication of Hooghiemstra et al [25]. The institutional review board approved this study, and all patients were informed and provided written consent.…”
Section: Methodsmentioning
confidence: 99%
“…It has been speculated that the occurrence of cerebral infarction (CI) caused by most heart diseases may be associated with the reduction of cardiac output (1). Hooghiemstra et al (2) think that the hemodynamic balance of the 'heart-brain axis' is the key factor in maintaining brain structure and any node problem may lead to cerebrovascular disease in the vascular pathway from the heart to the brain. Recent studies have indicated that left ventricular diastolic (LVD) dysfunction may occur in hypertensive patients when their heart structure is still normal (3).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CAO were selected from the Heart-Brain Connection (HBC) study, which is a multicenter cohort study in the Netherlands that focusses on the relation between cardiovascular and hemodynamic measures and cognitive impairment. 7 From all consecutive patients with CAO who participated in the HBC study from November 2014 to March 2017 (data release 1 October 2017), we included all patients with CAO who had experienced an ipsilateral transient ischemic attack (TIA) or nondisabling ischemic stroke more than six months before inclusion. CAO was defined as a complete occlusion of the internal carotid artery and was measured either with ultrasound, magnetic resonance angiography or computed tomography angiography.…”
Section: Methodsmentioning
confidence: 99%
“…The HBC study and SMART study were approved by the Ethics Committee of the Leiden UMC and UMC Utrecht, respectively. 7,8 All patients provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%